The smart village concept from 1.0 to 4.0 in the context of ICT entrepreneurship development in the Polish villages - Hanna Godlewska-Majkowska; Agnieszka Komor; Patrycjusz Zarębski (International Entrepreneurship Review)
Objective: The article aims to show the development process of smart villages from 1.0 to 4.0, analogous to the smart cities development, along with indicating the conditions of this process. Moreover, the goal was to examine how ICT enterprises influence the development of smart villages at the 1.0 level in rural areas and what their connections are with other sections of economic activity (based on the example of Poland).